The Biological fertilizer research results of Seabuckthorn (Hippophae rhamnoides) - Lantuu, Galt; Badam, Ninj; Mijidorj, Ankhtuya (Mongolian Journal of Agricultural Sciences, 2021)
The seabuckthorn subspecies mongolica used in this research. Seabuckthorn (Нippophae ramnoides L.) root nodule research focused on symbiotic nitrogen fixation bacteria that could aid in the cultivation of this species. Seabuckthorn root nodules have Frankia actinorhizal microorganisms.Under nitrogen-free conditions, seabuckthorn seedlings inoculated with a homogenate of root nodules that grew normally and the fresh weight of root nodules had positively correlated with plant growth. In the field, nitrogenase activity in root nodules was high in the period from June to September,when air temperatures were high and photosynthesis was active. Also we investigated the effect of nitrate on nitrogenase activity in seabuckthorn root nodules. Root nodules with many lobes were found in mature seabuckthorn trees grown in the field. Чацаргана (Hippophae Rhamnoides) тарьсан талбайд биологийн бордоо хэрэглэсэн дүнгээс Чацарганы (Hippophae rhamnoides) үндэсний булцуунаас азот шингээгч бактерийг ялган өсгөвөрлөх, шингээх идэвхи нь өөрчлөгдөж буй эсэхийг лабораторийн нөхцөлд турших, биобордоо бэлтгэж чацарганы тарьц суулгацыг бордож туршин үр дүнг хяналтын ургамалтай харьцуулж гаргахад VI,VII,VIII сард өссөн үзүүлэлттэй буюу 3,74-7,1 х 106 бактерийн эсээр нэмэгдсэн байна. Түлхүүр үг: Булцуу, биологийн бордоо, эрдэс бордоо,бичил биетэн